PERANCANGAN MEDIA KOMUNIKASI VISUAL ORANG TUA SAHABAT ANAK REMAJA DI MASA PANDEMI - Karlina, Nichi Hana (Universitas Komputer Indonesia, 2021)
One of the community forums that can become a vehicle for community empowerment through various programs that lead to efforts to change people's attitudes, behavior and way of thinking (mindset) in a better direction is KB Village. One of the activities carried out by Kampung KB is Youth Family Development (BKR). Program Bina Keluarga Remaja (BKR) is the concern of Kampung Ceria KB during the pandemic because teenagers can only stay at home, not infrequently this causes problems between teenagers and their parents, the BKR program has material about parents being friends of children who can minimize the problems that usually occur between parents and teenagers, but counseling activities still use traditional counseling media. This design aims to disseminate BKR program material regarding the friendship of parents and teenagers through social media content that is easily accessible to the public. In collecting data, this design uses qualitative methods by conducting interviews with the head of the Kampung KB Ceria, residents of RW 02, TKP Bojongloa Kidul District, and Psychologist Puspaga Bandung. The results of this design can be seen that the media used works quite optimally, both in terms of access, distribution, and outreach, so that it is effective in disseminating the BKR program material for Kampung Ceria